2021
DOI: 10.1089/dna.2021.0370
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of FABP5 Suppresses the Proliferation and Induces the Apoptosis of Gastric Cancer Cells Through the Hippo Signaling Pathway

Abstract: Fatty acid binding protein 5 (FABP5) has been reported to play an important role in various cancers. We found that high FABP5 expression was associated with poor histological differentiation and vascular invasion. High FABP5 expression indicated a poor prognosis. Downregulation of FABP5 suppressed cell proliferation, cell migration and invasion, and induced cell apoptosis. Bioinformatic analysis revealed that the Hippo signaling pathway was related to FABP5. We found that overexpression of yes-associated prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…FABP5 silencing has been shown to decrease cell proliferation and lead to cell cycle arrest in gastric cancer. [27] In breast cancer, FABP5 activates VEGF and upregulates EGFR expression, in turn, increasing PPAR to promote cancer progression [28]. Similar phenomena are reported in prostate cancer, showing that FABP5 activates PPARγ and upregulates VEGF [29].…”
Section: Discussionmentioning
confidence: 76%
“…FABP5 silencing has been shown to decrease cell proliferation and lead to cell cycle arrest in gastric cancer. [27] In breast cancer, FABP5 activates VEGF and upregulates EGFR expression, in turn, increasing PPAR to promote cancer progression [28]. Similar phenomena are reported in prostate cancer, showing that FABP5 activates PPARγ and upregulates VEGF [29].…”
Section: Discussionmentioning
confidence: 76%
“…24 The transcriptional coactivator YAP of the Hippo signaling pathway associated with cell proliferation and organ size is an established oncoprotein in GC. 25,26 Taken together,…”
Section: Ta B L Ementioning
confidence: 89%
“…Cyclin B1 drives cell cycle progression through the G2/M checkpoint, 23 and its high levels in GC cells are associated with accelerated G2/M transition 24 . The transcriptional coactivator YAP of the Hippo signaling pathway associated with cell proliferation and organ size is an established oncoprotein in GC 25,26 . Taken together, HSPA6 promotes the proliferation of GC cells via activating the Hippo pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have investigated the role of FABP5 in cancer, and most concluded that FABP5 displays enhanced activity in multiple cancers, such as prostate cancer (O'Sullivan & Kaczocha, 2020), breast cancer (R.‐Z. Liu et al, 2011), liver cancer (Seo et al, 2020) and gastric cancer (W. Wang, Liu, et al, 2021), by affecting fatty acid metabolism to promote cancer cell proliferation and migration. To support cell proliferation, cancer cells always undergo metabolic reprogramming, thereby producing large amounts of fatty acids, especially in CC (Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%